Economic impact of oil trade in a developing country: an empirical investigation of consequences of recent Gulf crisis in Malaysia - Abdul Rashid, Zakariah; Othman, Mohd Shahwahid (Penerbit Universiti Kebangsaan Malaysia, 1994)
Petroleum-based industry has become significant to the Malaysian economy since the early seventies. It is now one of the key industries in the economy. The economy's export ratio of oil quadrupled to 16 percent in 1988 from 4 percent in 1974. The country is now a net exporter of oil and gas but a net importer of petroleum products. This paper attempts to present the results of our empirical inquiry into the impact of an increase in oil price to the economy. Using the interindustry input-output model, the paper found that the net effect of an increase in oil surplus and a deficit in petroleum products trade provides strong potential for expanding output and employment.